1991
DOI: 10.1111/j.1439-0329.1991.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Armillaria rhizomorphs in Wisconsin aspen sucker stands

Abstract: bstract Weights of rhizomorphs of wndttervamtd Armillaria sp. obtained using ring-trench and core soil sampling methods around aspen stumps in stands at different intervals after harvest were correlated. The core method was used to sample a second series of stands twice (at an interval of two growing seasons) at radial distances of 0.5, 1.0, and 1.5 meters from stump centers. Stands were uncut (at both samplings) or 3, 6, 9, 12, or 15 years after harvest (at the time of the initial sampHng). Rhizomorphs were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In managed Norway spruce stands in the Swiss Alps, Prospero et al (2003a) found that the rhizomorph network formed by A. cepistipes can be very dense, reaching up to 25 m/m 2 . Similarly, Stanosz and Patton (1991) evidenced an abundant presence of soil rhizomorphs around stumps in managed aspen (Populus spp.) stands in Wisconsin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In managed Norway spruce stands in the Swiss Alps, Prospero et al (2003a) found that the rhizomorph network formed by A. cepistipes can be very dense, reaching up to 25 m/m 2 . Similarly, Stanosz and Patton (1991) evidenced an abundant presence of soil rhizomorphs around stumps in managed aspen (Populus spp.) stands in Wisconsin.…”
Section: Discussionmentioning
confidence: 97%
“…For example, when native forests are converted to exotic plantations, indigenous Armillaria species can cause considerable tree mortality (e.g., Armillaria root rot in Pinus radiata stands in New Zealand; Van der Pas 1981). The creation of fresh stumps through sylvicultural operations provides new food-bases for Armillaria species and stimulates the production of rhizomorphs in the soil (Stanosz and Patton 1991). Forest management may also modify the natural balance between different Armillaria species, sometimes resulting in pathogenic behavior by hitherto preferentially saptrotrophic species (Legrand et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This probably explains why liming increased food base colonization frequency only in plots with a low proportion of the BA in sugar maple. The 10-year delay between the establishment of plots and our study was long enough for the food bases to be colonized by Armillaria and for the buildup of the rhizomorph population in the soil (Pronos and Patton, 1977;Stanosz and Patton, 1991). Thus, the greater abundance of food bases in plots limed and/or dominated by sugar maples explains partially the greater frequency of rhizomorphs in the soil, and their increased ability to regenerate in laboratory conditions or to colonize maple stakes in situ in the forest floor.…”
Section: Discussionmentioning
confidence: 71%
“…This was expected in the light of the abundant literature that shows that abundance of rhizomorphs in soil strongly increases the probability of colonization of nearby wood pieces and, in particular, stumps by Armillaria ( Pronos and Patton 1978; Twery et al. 1990; Stanosz and Patton 1991; Marçais and Wargo 2000). It would thus appear that the former stand history, and in particular the pattern of stump colonization at the final felling of the previous stand, were the main factors determining the spatial pattern of collar colonization by the A. gallica epiphytic rhizomorphs in that stand.…”
Section: Discussionmentioning
confidence: 88%